INSECTICIDAL ACTIVITY OF EUCALYPTUS SP. VOLATILE OIL AGAINST BACKSWIMMER INSECT ANISOPS SARDEA - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The objective of this study was to evaluate a natural bio-insecticide manufacturing from Eucalyptus sp. volatile oil. The use of Eucalyptus sp. against the Backswimmer insect Anisops sardea Herrich-Schaeffer, 1849 predatory of larvae of common carp fish, Cyprinus carpio L., in artificial closed ponds in Babylon province represented a new idea in Iraq. The volatile oil of the Eucalyptus sp. was extracted by hot water method using the Clevenger, three concentrations of 250000, 450000 and 650000 ppm with benzyl benzoate as a stabilizer were used, which has a boiling point of 324OC (slow evaporation) at field experiment.The results of field and laboratory experiments of the extracted volatile oil in different concentrations, showed that the lower concentration used, the longer exposure time should be, the lowest experimental concentration (250000) ppm was effective for killing half the number of LC50 insects in the field after 30 minutes, with less concentration LC50 killer for laboratory insects 20 minutes after exposure. While the killing rate did not exceed 2.7% at laboratory experiment and 1.5% at field experiment with regard to the effect of the volatile oil on fish larvae was at all times and for different experimental concentrations. A gas chromatography detection of the active compounds that found in the volatile oil of Eucalyptus was performed. The results showed that it contained the following compounds: sabinen (0.06%), terpinen (2%), camphenin (3.4%), lemonine (1.08%), myrcine (0.62%), alph-pinene (10%), linalool (0.027%), camphor (6.9%).